Posterior First Infundibular Dissection: Another Safe Approach in Laparoscopic Cholecystectomy - Kashif Nadeem, Javed Mirdad Tarar, Muhammadrashid (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To test the efficacy of posterior infundibular dissection during Laparoscopic cholecystectomy Place and duration of the study: Surgical ward of Bakhtawar Amin Trust Teaching Multan for 1 year Study design: A retrospective study Methodology: A total of 150 patients undergoing laparoscopic cholecystectomy were included in the study. Firstly, the bile duct, Calot's node and gallbladder neck were identified along with the lower third of the common duct. An incision was made in the peritoneum anterior to the Calot's node at infundibulum and extended laterally and posteriorly. By retracting the gallbladder cephalad and medially, dissection continued in avascular plane between posterior wall of gall bladder and posterior branch of cystic artery. Anteriorly, a plane is created above the calot’s node and inferior to cystic artery, which was facilitated by posterior dissection of infundibulum. Posterior clipping and division of the cystic artery and duct was done. The rest of the gallbladder was dissected from the liver. Results: 120 patients (80%) had an elective LC status and 30 patients (20%) underwent an emergency LC. 2 patients (1.3%) underwent subtotal cholecystectomy.26 patients (18%) underwent MRCP due to suspicion of stones. Out of these 26 patients, 3 patients (11.5%) underwent ERCP due to the presence of stones.No bile duct injury was recorded. Conclusion: Posterior first infundibular dissection reduces the risk of bile duct injury and ensures safe laparoscopic cholecystectomy. Keywords: Laparoscopic cholecystectomy, infundibular dissection, bile duct injury, cholecystectomy, safe calot’s dissection.